Prevalence of Cryptosporidium spp., Enterocytozoon bieneusi, Encephalitozoon spp. and Giardia intestinalis in Wild, Semi-Wild and Captive Orangutans (Pongo abelii and Pongo pygmaeus) on Sumatra and Borneo, Indonesia - Mynářová, Anna; Foitová, Ivona; Kváč, Martin; Květoňová, Dana; Rost, Michael; Morrogh-Bernard, Helen; Nurcahyo, Wisnu; Nguyen, Cathleen; Supriyadi, Supriyadi; Sak, Bohumil (PloS one, 2016)
BACKGROUND: Orangutans are critically endangered primarily due to loss and fragmentation of their natural habitat. This could bring them into closer contact with humans and increase the risk of zoonotic pathogen transmission. AIMS: To describe the prevalence and diversity of Cryptosporidium spp., microsporidia and Giardia intestinalis in orangutans at seven sites on Sumatra and Kalimantan, and to evaluate the impact of orangutans' habituation and location on the occurrence of these zoonotic protists. RESULT: The overall prevalence of parasites in 298 examined animals was 11.1%. The most prevalent microsporidia was Encephalitozoon cuniculi genotype II, found in 21 animals (7.0%). Enterocytozoon bieneusi genotype D (n = 5) and novel genotype Pongo 2 were detected only in six individuals (2.0%). To the best of our knowledge, this is the first report of these parasites in orangutans. Eight animals were positive for Cryptosporidium spp. (2.7%), including C. parvum (n = 2) and C. muris (n = 6). Giardia intestinalis assemblage B, subtype MB6, was identified in a single individual. While no significant differences between the different human contact level groups (p = 0.479-0.670) or between the different islands (p = 0.992) were reported in case of E. bieneusi or E. cuniculi, Cryptosporidium spp. was significantly less frequently detected in wild individuals (p < 2×10-16) and was significantly more prevalent in orangutans on Kalimantan than on Sumatra (p < 2×10-16). CONCLUSION: Our results revealed that wild orangutans are significantly less frequently infected by Cryptosporidium spp. than captive and semi-wild animals. In addition, this parasite was more frequently detected at localities on Kalimantan. In contrast, we did not detect any significant difference in the prevalence of microsporidia between the studied groups of animals. The sources and transmission modes of infections were not determined, as this would require repeated sampling of individuals, examination of water sources, and sampling of humans and animals sharing the habitat with orangutans.
Keywords: Enterocytozoon; Prevalence; Cryptosporidium; prevalence; nemoci lidoopů; Indonésie; Pongo pygmaeus; Encephalitozoon; Borneo; protozoální infekce zvířat; parazitární nemoci střev; Giardia lamblia; Protozoan Infections, Animal; Ape Diseases; zvířata; Humans; Pongo abelii; Indonesia; Intestinal Diseases, Parasitic; lidé; Animals